Implementasi Metode Sorogan dalam Membaca Kitab Kuning - Wuni Arum Sekar Sari; Arifah Tazkiatul Fikriyah (Indonesian Journal of Humanities and Social Sciences, 2022)
The sorogan method is considered a very effective learning method in the yellow book education process in Pondok Pesantren, because the implementation of the sorogan technique is based on the main purpose of accuracy in reading, accuracy in understanding the content, and accuracy in revealing the contents of the reading. The application of this sorogan method in Pondok Pesantren prioritizes strong emotional relationships and deep observations between educators and students. Field studies incorporate research. Observation, recording, and interviewing are techniques used by researchers. Qualitative approaches are also carried out in data analysis. The students of Pondok Pesantren Hidayatul Mubtadi'in Al Mahrusiyah who learned to read the yellow book could benefit greatly from Sorogan's approach, according to the study findings.